Human Metapneumovirus Infection in Jordanian Children: Epidemiology and Risk Factors for Severe Disease. Issue 12 (December 2015) - Schuster, Jennifer E.; Khuri-Bulos, Najwa; Faouri, Samir; Shehabi, Asem; Johnson, Monika; Wang, Li; Fonnesbeck, Christopher; Williams, John V.; Halasa, Natasha
Abstract : Background: Human metapneumovirus (HMPV) is a leading cause of acute respiratory tract infection in young children. Our objectives were to define HMPV epidemiology and circulating strains and determine markers of severe disease in Jordanian children. Methods: We conducted a prospective study from March 16, 2010 to March 31, 2013 using quantitative reverse transcription-polymerase chain reaction to determine the frequency of HMPV infection among children <2 years old admitted with fever and/or acute respiratory illness to a major government hospital in Amman, Jordan. Results: HMPV was present in 273 of 3168 (8.6%) of children presenting with acute respiratory tract infection. HMPV A2, B1 and B2, but not A1, were detected during the 3-year period. HMPV-infected children were older and more likely to be diagnosed with bronchopneumonia than HMPV-negative children. HMPV-infected children with lower respiratory tract infection had higher rates of cough and shortness of breath than children with lower respiratory tract infection infected with other or no identifiable viruses. Symptoms and severity were not different between children with HMPV only compared with HMPV coinfection. Children with HMPV subgroup A infection were more likely to require supplemental oxygen. In a multivariate analysis, HMPV subgroup A and age <6 months were independently associated with supplemental oxygen requirement. Conclusions: HMPV is a leading cause of acute respiratory tract disease in Jordanian children <2 years old. HMPV A and young age were associated with severe disease. Ninety percent of HMPV-infected hospitalized children were full term and otherwise healthy, in contrast to high-income nations; thus, factors contributing to disease severity likely vary depending on geographic and resource differences. Abstract : Supplemental Digital Content is available in the text.